Linear function in case of more than two sets - Mohammad Osama Ahmad Alkatib (College of Education for Pure Sciences, 2010)
Abstract This research dealt with new manner to distinguish among digital photos through Wilks Lambda test. In this way we will know the distinguishing function i.e. its ability to distinguish among digital photos. Then there will be a move to the second stage which represents finding the distinguishing function, which will be used to distinguish among digital photos. After that Mohalanobis scale will be used to know the distance between any communities (i.e. two photos). And in the final stage we will catch the classification mistakes resulted from distinguishing function.